Mechanical loading of intervertebral disc modulates microglia proliferation, activation, and chemotaxis. Issue 7 (July 2018) - Navone, S.E.; Peroglio, M.; Guarnaccia, L.; Beretta, M.; Grad, S.; Paroni, M.; Cordiglieri, C.; Locatelli, M.; Pluderi, M.; Rampini, P.; Campanella, R.; Alini, M.; et al.
Summary: Objective: The aim of the study is to assess the effects of the neuroinflammatory microenvironment of a mechanically-induced degenerating intervertebral disc (IVD) on neuroinflammatory like cells such as microglia, in order to comprehend the role of microglial cells in degenerative disc disease. Methods: Bovine caudal IVDs were kept in culture in an ex vivo bioreactor under high frequency loading and limited nutrition or in free swelling conditions as control samples. Conditioned media (CM) were collected, analysed for cytokine and neurotrophin content and applied to microglial cells for neuroinflammatory activation assessment. Results: Degenerative conditioned medium (D-CM) induced a higher production of interleukin (IL)-8, nerve growth factor (NGF), interferon (IFN)-γ, IL-17 from IVD cells than unloaded control conditioned medium (U-CM). Upon 48 h of co-incubation with microglia, D-CM stimulated microglia proliferation, activation, with increased expression of ionized calcium binding adaptor molecule 1 (IBA1) and CD68, and chemotaxis. Moreover, an increment of nitrite production was observed. Interestingly, D-CM caused an upregulation of IL-1β, IL-6, tumour necrosis factor α (TNFα), inducible NO synthase (iNOS), IBA1, and vascular endothelial growth factor (VEGF) genes in microglia. Similar results were obtained when microglia were treated with the combination of the measured cytokines. Conclusions: Our findings show that in IVD degenerative microenvironment, IL-8, NGF, IFN-γ, IL-17 drive activation of microglia in the spinal cord and increase upregulation of neuroinflammatory markers. This, in turn, enhances the inflammatory milieu within IVD tissues and in the peridiscal space, aggravating the cascade of degenerative events. This study provides evidence for an important role of microglia in maintaining IVD neuroinflammatory microenvironment and probably inducing low back pain.